Unilateral Subfrontal Approach for Giant Tuberculum Sellae Meningioma: Single Center Experience and Review of the Literature - Xiao, Feng; Shen, Jie; Zhang, Luyuan; Yang, Jiqi; Weng, Yuxiang; Fang, Zebin; Zhang, Chao; Ye, Hongxing; Zhan, Renya; Zheng, Xiujue (Frontiers in Oncology, 2021)
Background：Microsurgical Transcranial approach (mTCA) is the primary choice for the resection of giant Tuberculum Sellae Meningiomas (TSM). The objective of this study is to explore surgical details of unilateral subfrontal approach. Methods：Nine patients with giant TSM treated by unilateral subfrontal approach were included from January 2018 to January 2020. Demographic characteristics, surgical data, post-procedure complications and outcomes of patients have been descriptive analyzed, combined with systematic literature review to explore the surgical details and the prognosis of unilateral subfrontal approach. Results：Nine patients include five male and four females, age range from 35 to 77 years, duration of visual impairment from 1 to 12 months, were all peformed unilateral subfrontal approach. Eight patients achieved radical resection (Simpson grades I-II) through post-operative imaging confirmation, and Simpson IV resection was performed in the remaining one due to cavernous sinus invasion. The postoperative visual acuity was improved or maintained in 7 patients. Visual acuity decreased in 2 cases, including 1 case of optic nerve atrophy and the other case of optic canal not opening. 5 cases with frontal sinus opened were repaired during the operation and there was no postoperative cerebrospinal fluid leakage or intracranial infection. One patient suffered from postoperative anosmia, one patient developed left limb weakness, but their symptoms have improved in the follow-up. Conclusion：Summarize the experience of our center and previous literature, unilateral forehead bottom craniotomy is a feasible surgical approach for giant tuberculum sellae meningioma. Intraoperative application of EC glue and pedicled fascia flap to repair the frontal sinus can prevent complications associated with frontal sinus opening. Optic canal unroofing has huge advantage in visual improvement.